Visitors' preferences and recreation values for nature recreation in Mountain Parks, Sabah - Wong, Wilson Vun Chiong (2011)
Natural attractions determine the potentials and opportunities of recreation and nature tourism development in mountain parks. Visitors' preferences on natural attractions are important to the development of recreational facilities and estimates of recreation values justify the development. This study aimed at identifying visitors' preferences and estimating the recreation values of natural attractions in Kinabalu Park and Crocker Range Park, Sabah. Analytical Hierarchy Process was applied to examine the visitors' preferences on natural attractions of flora, wildlife and scenery. Scenery-viewing (39.2%) is most preferred among visitors followed by wildlife-watching (32.2%) and flora-viewing (28.5%). GIS-based viewshed analysis was then employed for assessing the visible area of selected trails in the two parks. It is revealed that trails in Kinabalu Park are superior to trail in Crocker Range Park in terms of visible area. Contingent Valuation Method was applied to elicit the recreation values of the attractions. It is found that the recreation value for wildlife-watching is the highest among the attractions and the recreation values for all three attractions in Kinabalu Park are higher than Crocker Range Park. This study suggested that the development of recreational activities in parks must meet according to the visitor's preferences